Grolier business library ([Danbury, Conn.] : Grolier Inc, ., 1987)
We all want to live our lives in our own way. The problem is that so much of the time, other people, events and circumstances seem to maneuver us into situations in a certain way. We feel manipulated, controlled, helplessly stuck in our own lives and yet unable to make things happen the way we want. The secret lies in realising that we can't change other people. The answer lies in ourselves, and changing ourselves so we are ready to cope with all that life and other people throw at us. This set in 20 volumes helps us to manage the different situations in our lives.
Each volume has a different title.
Vol. 1 Management : theory and practice / by Ernest Dale. -- Vol. 2 The world of business / by Dan Steinhoff. -- Vol. 3 Economics for managers / by Charles J. Stokes. -- Vol. 4 Strategy management / by Kevin W. Tourangeau. -- Vol. 5 The executives's accounting primer / by Robert L. Dixon. -- Vol. 6 Guide to financial analysis / by Oswald D. Bowlin, John D. Martin, and David F. Scott. -- Vol. 7 Fundamentals of marketing / by William J. Stanton. -- Vol. 8 Advertising in the marketplace / by John D. Burke. -- Vol. 9 Textbook of salesmanship / by Frederic A. Russell, Frank H. Beach and Richard H. Buskirk. -- Vol. 10 Retailing management / by Larry D. Redinbaugh. -- Vol. 11 Information systems concepts for management / by Henry C. Lucas. -- Vol. 12 Introduction to business data processing / by Lawrence S. Orilia. -- Vol. 13 Computers in business / by Donald H. Sanders. -- Vol. 14 The manager's guide to statistics and quantitative methods / by Donald W. Kroeber and R. Lawrence LaForge. -- Vol. 15 Industrial organization and management / by James L. Riggs [and others]. -- Vol. 16 Human resource planning / by James W. Walker. -- Vol. 17 Human behavior at work / by Keith Davis. -- Vol. 18 Effective business communications / by Herta A. Murphy and Charles E. Peck.-Vol. 19 Leadership : what effective managers really do.. and how they do it / by Leonard R. Sayles. -- Vol. 20 Index.-
Includes bibliographical footnotes and index.
oif 13/11/2019
Ref.
Keywords: Business -- Encyclopedias; Finance -- Encyclopedias; Commerce -- Encyclopedias; Industrial management